A new species of Pleurothallis (Orchidaceae: Pleurothallidinae) from Ecuador - Doucette, Alfonso; Portilla, Jose; Medina, Hugo; Cameron, Kenneth M. (Phytotaxa, 2017)
A new species, superficially similar to Pleurothallis allenii, and best attributed to Pleurothallis sect. Pleurothallis subsect. Acroniae ser. Amphygiae, is described here as Pleurothallis flavomarginata. The new species was discovered under cultivation at the orchid nursery Ecuagenera. The new species is described, illustrated, and distinguished from similar species based on its morphological distinctness.